PREFERENSI PENGUNJUNG TERHADAP PELAYANAN DI GRHATAMA PUSTAKA YOGYAKARTA - Sabda Elisa Priyanto; Eko Sugiarto (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2020)
The purpose of this paper is to describe the preferences of visitors to the service quality at Grhtama Pustaka Yogyakarta. The library has a function as a place of recreation that should be able to provide good services to visitors. The services provided must be based on visitor preferences when visiting and getting services. Visitor preferences for service quality that is tangible, reliability, responsiveness, assurance, and empathy. Grhtama Pustaka as the largest library in Yogyakarta must be able to provide good services, as a form of support to become a place of recreation in Yogyakarta. The method in this research is a descriptive study, with a population of visitors to Grhatama Pustaka, selected by the probability sampling method with a simple random sample technique, by interviewing 118 visitors. The results of this study found that tourist preferences for services in Grhatama Pustaka in the tangible part are strong preferences for visitors to visit, while the reliability, responsiveness, assurance, and empathy factors in library services are good preferences for visitors who need library services. Furthermore, hospitality services are needed if the manager wants to make visitors make Grhatama Pustaka a choice of the recreation area.Keywords: Preference, Visitor, Service Quality, Library